Murals as a tourist attraction in a post-industrial city – a case study of Łódź (Poland) - Jażdżewska , Iwona (Turyzm/Tourism, 2017)
The article presents the development of Łódź murals in the 21st c. and the opinions of the participants of tours organized in 2014 by the Urban Forms Gallery. Their objectives include saturating the urban fabric with street art and promoting this form of artistic expression. Having analysed memories registered and shared on YouTube, information published by local, national and foreign media, opinions posted by tourists and street-art lovers in online blogs and galleries, as well as the information about some artists on their websites, the author studied the opinions of tour participants as well and established the significance of Łódź murals. The analysis enabled her to look for the answer to the question whether murals can be a tourist attraction in a post-industrial city like Łódź.